Analysis of the Effect of Service Quality and Product Quality on Consumers (Case Study of Consumers Cv Central Elektro Bengkulu) - Subandrio Subandrio; Teza Pebodera (Penerbit Jurnal Indonesia, 2022)
This thesis is entitled Analysis of the influence of Service Quality and Product Quality on Consumer Satisfaction of Cv central electro bengkulu consumers. The purpose of this research is to develop and prove the knowledge of the theoretical sciences learned in college and applied to the world of work. The object of this research is Consumers from CV Central Elektro Bengkulu, this research method is descriptive analysis which is applied to quantitative methods, while the sampling technique of this study uses purposive sampling. The number of respondents used in this study were 85 respondents from electrical central CV consumers and using SPSS. By using multiple regression analysis, the results of this study can be concluded that the variables of service quality and product quality have a positive and significant effect on customer satisfaction, service quality has a positive effect on customer satisfaction, and product quality has a positive effect on customer satisfaction.